Human aspects of hospital management - Luis Hernan C. Pinochet; Claudia Raffa Galvão (O Mundo da Saúde, 2010)
This investigation aims to present a theoretical discussion on the interface between humanization and management in the domain of health. The adopted methodology has been the bibliographical survey, and we did a descriptive investigation and qualitative data analysis. After analyzing the collected data, we identified that health clients perceive the necessity to feel more welcomed and to be in a more humanized atmosphere. One thinks that the Institutions of Health will need to adapt to the new demands of that market. As results, we observed there is not some exclusive model of implementation of humanization in health, although their adoption is fundamental, and may create fidelization in patients/clients. The possible conclusion is that, as humanization a relatively new area, we still need to explore and learn more on the subject.